Analisis DSN MUI Nomor : 103/DSN-MUI/X/2016 Tentang Novasi Subyektik berdasarkan Prinsip Syariah - amin ok rais (ITB AAS INDONESIA Surakarta, 2022)
Social economics is a scientific discipline that cannot be separated from today's society. Moreover, everyone's economy is different. One of the problems is the delay in making payments even to a lack of funds which results in not being able to repay the debt. Therefore, an alternative emerged, namely through DSN MUI Number 103/DSN-MUI/X/2016 concerning Subjective Novation which discusses the replacement or new contract both in terms of subjectively active and subjectively passive. To strengthen the fatwa or decision above by mentioning and including several arguments as a basis. With qualitative methods and literature study the authors describe the understanding that can be drawn from the four hadiths. Based on the results of the study, there were many differences of opinion and did not directly lead to innovation. However, explicitly the DSN MUI fatwa Number 103/DSN-MUI/X/2016 regarding Sharia Novation has represented the previous fatwa, namely the MUI DSN Number 12/DSN-MUI/IV/200 regarding Hawalah and the MUI DSN Number 58/DSN-MUI/V /2007 on Hawalah bil Ujrah.